Analysis of Influence of Micro- and Macroenvironmental Factors on Activity of Enterprise of the Service Sector (through the example of LTD "Taxi-Vladivostok") ("Journal "U". Economy. Management. Finance.", 2017)
The article describes tools for analysis of micro- and macroenvironment of an enterprise. The analysis is illustrated by an example of a choice of strategy of development for an enterprise
Keywords: external environment; external factors; environment of influence; strategy of development